Symulacja komputerowa jako narzędzie sterowania rynkiem - Foryś, Jerzy (Wydział Prawa i Administracji UAM, 1983)
The study presents one of the stages of a process of systematic market research which consists, among others, of control understood as an intentional manipulation of the system which has to result in reaching its desirable state by means of obtaining determined values of variables of objective by variables of decision. The attempted construction of complex market model in a macroeconomic scale resulted in thirteen equasion final model which was used for market manipulation with the use of computer simulation. The simulation results are presented in three variants, differing as to the choice of desirable values of the exit vector, for the market of foodstuffs, alcoholic beverages and for the market in general in the 1980 -1985 span of time. Results of the presented research procedures proved a high degree of usefulness of complex market models not only in forecasting future results of certain moves and ventures but also in the simulation of market control in Poland.
Attempt at market control in the macroeconomic scale by means of a computer simulation